The Inducible Deletion of Drosha and MicroRNAs In Mature Podocytes Results In A Collapsing Glomerulopathy - Zhdanova, Olga (2011)
MiRNAs have been shown to play key roles in both the function and differentiation of a number of different cell types. Drosha and Dicer, two RNAase III enzymes, function in a stepwise manner to generate a mature miRNA. Previous studies have demonstrated that podocyte-specific deletion of Dicer during development results in a collapsing glomerulopathy (CG). However these studies did not address whether miRNAs are required for the normal function of a mature podocytes throughout life. In addition, Dicer has functions other than generation of miRNAs. We now show that a podocyte-specific deletion of Drosha results in a similar phenotype to Dicer mutants confirming that the Dicer mutant phenotype is due to the loss of miRNAs. Moreover, we demonstrate that inducible deletion of Drosha in 2–3 month old mice results in a CG, thereby demonstrating for the first time that miRNAs are required for the normal function of mature podocytes. The finding that loss of miRNAs in mature podocytes leads to a CG is consistent with the idea that changes in specific miRNAs in the various podocytopathies may directly mediate disease, and suggests that identifying these miRNAs will provide new insight into disease pathogenesis and novel therapeutic targets.